2000
DOI: 10.1177/154193120004401101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novice Driver CD-Rom Based Training Program: A Simulator Study

Abstract: The Monash University Accident Research Centre (MUARC) in Melbourne, Australia, recently completed research which culminated in the development of a CD ROM-based perceptual and cognitive skills training product for young novice car drivers. This paper describes the design of an experiment, using an advanced driving simulator located at MUARC, to evaluate the instructional effectiveness of the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nevertheless, some studies found that gender did not play a role in DSS symptoms ( 40 42 ). Motion sickness was recognized in some research as an influencing factor in increasing the possibility of simulator sickness ( 24 , 43 45 ). However, Frank et al stated that this factor may not affect DSS symptoms ( 40 , 41 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nevertheless, some studies found that gender did not play a role in DSS symptoms ( 40 42 ). Motion sickness was recognized in some research as an influencing factor in increasing the possibility of simulator sickness ( 24 , 43 45 ). However, Frank et al stated that this factor may not affect DSS symptoms ( 40 , 41 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of simulator education and training does appear to improve hazard perception skills (e.g. Carpentier, Wang, Jongen, Hermans, & Brijs, 2012;Chapman, Underwood, & Roberts, 2002;Fisher, Young, Zhang, Knodler, & Samuel, 2017;Pradhan, Fisher, & Pollatsek, 2006;Regan, Triggs, & Godley, 2000a, 2000bThomas et al, 2011). This education and training appears effective after four days (Pradhan et al, 2006) and four weeks (Carpentier et al, 2012;Regan et al, 2000b).…”
Section: Driving Simulatorsmentioning
confidence: 99%
“…Overall, research evidence suggests that hazard perception simulator training results in skill improvement, at least in the short term (e.g. Carpentier, Wang, Jongen, Hermans, & Brijs, 2012;Chapman, Underwood, & Roberts, 2002;Pradhan et al, 2006;Regan, Triggs, & Godley, 2000a, 2000bThomas et al, 2011). However, few studies have undertaken follow-up investigations and even fewer have investigated the transfer of skills from the simulator to onroad driving.…”
Section: Educationmentioning
confidence: 99%